2006
DOI: 10.1249/01.mss.0000228947.93270.2e
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Energy Expenditure in Women Using the MET System

Abstract: : In individuals with a TBF content typical for contemporary Western women, standard TEE is lower than proposed TEE. This bias increases as the TBF content of subjects increases. The results indicate that proposed TEE is more accurate than standard TEE, but this requires confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It may be that the accepted adjustments for body composition are simply not adequate and this becomes obvious when comparing two populations with such different body sizes and composition. Specifically, AEE is a product of the time spent in physical activity, the intensity of the physical activities, and the weight of the subject performing those physical activities (41,42). Thus a simple linear adjustment for weight may be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the accepted adjustments for body composition are simply not adequate and this becomes obvious when comparing two populations with such different body sizes and composition. Specifically, AEE is a product of the time spent in physical activity, the intensity of the physical activities, and the weight of the subject performing those physical activities (41,42). Thus a simple linear adjustment for weight may be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…BMR has been shown to increase as pregnancy progresses. 16,29,30 In a review by Butte based on 261 women from eight studies, it was found that the average increase in BMR was 4%, 10% and 24% during the first, second and third trimesters, respectively. 31 However, this increase in BMR is not always predictable and it may even decrease during the first part of pregnancy and persist into the second half of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, researchers have speculated that a MET for a specific activity may be lowered as pregnancy advances due to increases in basal metabolic rate (BMR) associated with pregnancy. 11 Despite these observations and the acknowledgment that the current MET system is not appropriate for use during pregnancy, 11,16 many pregnancy-related studies continue to utilize the MET system. [17][18][19][20] The current study builds on this prior work by including rest, additional activities of daily living and walking.…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported physical activity is commonly used in these studies to estimate energy expenditure, which is calculated indirectly using the multiple of MET by consulting the Compendium of Physical Activity 8 . However, Forsum et al 2 observed that the total energy expenditure of 15 healthy pregnant women at 32 weeks gestation predicted with the standard MET system was underestimated -multiplying BMR by the MET value and by the duration of the activity -when compared to the values obtained with the gold standard (doubly labeled water method).…”
Section: Introductionmentioning
confidence: 99%
“…According to Butte et al 1 , the traditional approach to the determination of nutritional requirements only considers the increase in the basal metabolic rate (BMR) of pregnant women, but may underestimate the true energy requirements since it does not consider energy expenditure during physical activity and the thermic effect of feeding. Thus, efforts have been made to determine not only the increase in the BMR during pregnancy, but also that resulting from physical exercise in order to potentiate its health benefits for the woman and child [1][2][3][4][5] . Since the leisure physical activity most commonly performed by women during pregnancy is walking 6 , studies have investigated the energy expenditure of women during this type of exercise.…”
Section: Introductionmentioning
confidence: 99%